Design Of A Cathodic Protection Against Corrosion For Marine And Offshore Structure - Muhamad Farizuddin Anwar bin Mansor, Muhamad Farizuddin (Universiti Teknologi PETRONAS, 2008)
Large marine structures and machineries such as oil platforms and ships use numerous ways to propagate or prevent corrosion, and one of the technique is Cathodic Protection (CP). For more than 50 years, CP has been employed to prevent corrosion on pipelines, storage tanks as well as buried and submerged metallic structures. It is the most effective and least expensive method for controlling corrosion. Large marine structures have probably the greatest application of cathodic protection, followed by marine machineries and equipments such as vessels and pipelines. As the technology progresses gradually, the application of CP increases as more structures being constructed or built around or even submerged in aggressive corrosion environment. Designs of CP were often based upon guesswork than the application of science. This condition serves as the basic of the project, with the aim of improving the performance of CP system by introducing new design of sacrificial anode CP block. This improvement is mainly achieved by increasing the protection area of the sacrificial CP anode block. The characteristic that will be improved is determined first, which acts as initial step of the project’s methodology. After the design has been completed, fabrication session commenced, followed by an experimental work and analysis of the corrosion protection effect on the new design. The experiments have been done using basic immersion technique, and the final results were obtained using FerroVer® method of the Powder Pillow Test. The result obtained from the analysis proved that the design modification upon the CP sacrificial block has a significant effect of improvement onto the corrosion protection performance.